Analisis Pengambilan Keputusan Mahasiswa Memilih Program Studi Pendidikan Ekonomi Universitas Bhinneka PGRI Tulungagung Tahun Akademik 2024/2025 - Putri, Shalsabila Adelia; Umami, Nailariza (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Choosing a study program is an important decision for students because it is related to their future education and career. Many students do not fully understand their interests and talents about what they choose. This study aims to determine students' decision-making in choosing an economic education study program and the factors that influence these decisions. This study uses a qualitative method with data collection techniques in the form of observation, interviews, and documentation. Data analysis is carried out through four stages, namely data collection, data reduction, data presentation, and data verification. The results of the study show that students' decision-making is influenced by internal factors (interests, motivation) and external factors (job prospects, information from alumni). Students' interests are mostly in line with their previous educational background and are supported by their parents. Dominant information is obtained from alumni, more than from social media. The decision to choose a study program is based on considerations that are closely related to these factors.